Investigation of Friction Welding Dissimilar AISI 304 and AISI 1040 Steels - Balalan, Zulkuf; Yaz, Mehmet; Buldağ, Sedat (My University, 2024)
Friction time is one of the important parameters in friction welding. The effect of friction time on the mechanical and microstructural properties of the weld was investigated in the friction welding of AISI 304 and AISI 1040 steels. With the enhancement of friction time, the temperature at the welding region naturally increased. Increasing the friction time resulted in the formation of a stronger weld. The highest tensile strength of 755 MPa was found in the S3 weld sample made at the highest friction time of 9 seconds. An increase in the friction time also provided a significant increase in the weld tensile elongation. S2 and S3 weld samples were broken as ductile during the tensile test, while S1 weld sample was broken as a mixture of brittle and ductile. The highest microhardness value of approximately 310 HV was determined at the joint area of the S1 weld produced with the lowest friction time. Hardness at the weld interface slightly decreased with an increase in the friction time. The weld interface shape changed depending on the friction time.
Keywords: Microhardness; microstructure; tensile strength; Friction welding; AISI 304 and AISI 1040 steels